Transcriptional analysis of human zeta globin genes. - Proudfoot, N; Rutherford, T; Partington, G (1984)
The human embryonic alpha-like globin gene (zeta) and a closely linked pseudogene (psi zeta) are located on chromosome 16. The psi zeta gene has a nonsense mutation in exon 1 but has identical promoter sequence and RNA processing sites to the zeta gene, raising the possibility that both psi zeta and zeta are transcriptionally active. We have studied transcription of the human zeta and psi zeta genes in a number of systems to examine their cell type specificity and enhancer requirement. (i) Cloned zeta and psi zeta genes transfected into human HeLa or monkey Cos7 tissue culture cells show no transcriptional activity. The presence of an SV40 enhancer does not activate the zeta promoter except at low levels when in very close proximity (less than 50 bp from the CCAAT box). (ii) In contrast to other tissue-specific genes tested to date, both zeta and psi zeta gene promoters initiate transcription efficiently when micro-injected into Xenopus oocyte nuclei. We suggest that embryonic-specific factors in the oocyte may permit efficient zeta gene transcription. Furthermore, the zeta promoter sequence from - 111 to + 38 bp is sufficient for transcription in this system.